Stoichiometry and doping mechanism of the cubic pyrochlore phase in the system Bi2O3–ZnO–Nb2O5 - Tan, Kar Ban; Lee, C. K.; Zainal, Zulkarnain; Miles, Gabrielle C.; West, Anthony Roy (Royal Society of Chemistry, 2005)
The subsolidus phase diagram of the system Bi2O3–ZnO–Nb2O5 in the region of the cubic pyrochlore phase has been determined at 950 °C. This phase forms a solid solution area that does not include the so-called ideal composition P, Bi3Zn2Nb3O14. It may be described in terms of two compositional variables: ZnO deficiency compared to P together with variable Bi : Nb ratio. Density measurements, preliminary crystallographic studies and the phase diagram indicate the solid solutions to have general formula, Bi3+yZn2−xNb3−yO14−x−y: −0.11(1) ≤ y ≤ 0.14(1) and −0.03(1) ≤ x ≤ 0.31(1).